Structural Equation Modeling in Evaluation of Technological Potential of European Union Countries in the years 2008-2012 - Adam P. Balcerzak; Michal Bernad Pietrzak (Institute of Economic Research (IER), 2016)
The abilities of countries to take advantage of global technological progress is currently the main growth determinant. It is especially important in the case of developed economies and the countries that concentrate on closing a development gap. As a result, there is a scientific need to make an international comparisons of countries' technological potential, which can be useful in pointing the economies that can be considered as the leaders and the economies that make especially quick progress in the field. Thus, the main purpose of the research is the identification of the variables that influence countries' technological potential at macroeconomic level, which can be used in its measuring. The second aim of the article is the evaluation of progress obtained by 'new' European Union member states. It is assumed that technological potential can be treated as a latent variable. Thus, it can be measured with application of Structural Equation Models (SEM). In the research, the hypothetic SEM model was proposed for the European Union countries in the years 2008-2012. The model was estimated with application of seven variables sugested by Eurostat as the potential measures of technological potential of the EU economies. The research confirmed significant influence of five of the given variables. Additionally, the research showed some progress in the field obtained by Central European countries that joined the EU after the year 2004.
Keywords: C30; C38; O14; 330; structural equation model (SEM); technology; technological potential; European Union